2020
DOI: 10.1002/chem.202001056
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Lanthanum Complexes on a Functionalized Graphene Surface: Theoretical Investigation on Ethylene and 1,3‐Butadiene Homo‐ and Co‐Polymerization

Abstract: In this contribution, we describe the use of graphene as an efficient catalyst support and the role it plays in increasing the Lewis acidity of the supportedm etal complexes.B yadensity functional theorys tudy,w eshowt hat the [La(N(SiMe 3) 2) 3 ]c omplex can be easily grafted on graphene-OHa nd-COOHf unctionalized surfaces. Twos table mono-grafted compounds, (gO)-[La(N(SiMe 3) 2) 2 ]a nd (gOO)-[La(N(SiMe 3) 2) 2 ], are formed, behaving as stronger Lewis acids than the previously reported silica grafted analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 93 publications
(215 reference statements)
0
4
0
Order By: Relevance
“…31 A recent theoretical study examined the immobilization of La[N(SiMe 3 ) 2 ] 3 on graphene system and the catalytic activity of methylated species in ethylene and 1,3butadiene polymerization. 32 ■ RESULTS AND DISCUSSION Tetraisobutylaluminate Precursors. Complexes of the type Ln[N(SiMe 3 ) 2 ](HAliBu 3 )(AliBu 4 ) (Ln = La, Pr, Nd) (1 Ln ) recently reported by our group display the first examples of ancillary ligand-free, trivalent lanthanide isobutylaluminates.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 A recent theoretical study examined the immobilization of La[N(SiMe 3 ) 2 ] 3 on graphene system and the catalytic activity of methylated species in ethylene and 1,3butadiene polymerization. 32 ■ RESULTS AND DISCUSSION Tetraisobutylaluminate Precursors. Complexes of the type Ln[N(SiMe 3 ) 2 ](HAliBu 3 )(AliBu 4 ) (Ln = La, Pr, Nd) (1 Ln ) recently reported by our group display the first examples of ancillary ligand-free, trivalent lanthanide isobutylaluminates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gauvin et al applied similar materials TIBA@Nd­[N­(SiMe 3 ) 2 ] 3 @silica (Ln = Y, La, Nd, Sm) as catalysts for the polymerization of methyl methacrylate, ethylene, ε-caprolactone, and isoprene . A recent theoretical study examined the immobilization of La­[N­(SiMe 3 ) 2 ] 3 on graphene system and the catalytic activity of methylated species in ethylene and 1,3-butadiene polymerization …”
Section: Introductionmentioning
confidence: 99%
“…Complexes Ln[N(SiMe 3 ) 2 ] 3 are favourably activated by TIBA, upon addition of a fluorinated borate cocatalyst 7–9 or silica grafting. 10–12 Both selectivity and activity of Ln[N(SiMe 3 ) 2 ] 3 /TIBA-derived ternary mixtures are found to be superior or at least comparable with established catalyst systems based on lanthanide carboxylates. 7 Moreover, ternary system (2-Ph-indenyl) 2 Gd[N(SiMe 3 ) 2 ]/[Ph 3 C][B(C 6 F 5 ) 4 ]/TIBA bearing a silylamido ligand was described as a highly efficient catalyst for cis -1,4-selective polymerization of butadiene (>99%).…”
mentioning
confidence: 94%
“…On the other hand, to overcome the drawbacks of the homogeneous catalysts in catalyst contamination in reaction outcomes and poor recyclability, increasing interest has been directed toward developing supported catalysts in surface organometallic chemistry (SOMC). Such catalysts not only show the high activity of homogeneous catalysts but also display the ease of separation and recyclability of heterogeneous catalysts, allowing for better control of the whole synthetic process. Consequently, the immobilized heterogeneous rare-earth metal complexes have received much interest in SOMC and have demonstrated interesting performance in organic synthesis and polymerization. Very recently, we developed the well-defined silica-grafted rare-earth metal benzyl materials Ln­(CH 2 C 6 H 4 NMe 2 - o ) 3 @SBA-15 (Scheme ) and found that they exhibited extremely high selectivity and good recyclable property in the transformation of primary arylsilanes into secondary arylsilanes through redistribution. , This interesting finding prompted us to explore their catalytic potential in other organic transformations. Inspired by the elegant work reported by the Marks group and the Chen group using rare-earth metal complexes Ln­[N­(SiMe 3 ) 2 ] 3 as catalysts in amide reduction, , it was envisaged that Ln­(CH 2 C 6 H 4 NMe 2 - o ) 3 @SBA-15 (Ln–C σ-bonded species) possesses promising catalytic performance in amide reduction owing to its bond disruption enthalpy comparable to the amide analogues (Ln–N σ-bonded complexes) .…”
Section: Introductionmentioning
confidence: 99%